1995
DOI: 10.21273/jashs.120.6.1087
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Cropping in `Loadel' Cling Peach Using Gibberellin: Effects on Flower Density, Fruit Distribution, Fruit Firmness, Fruit Thinning, and Yield

Abstract: Whole-tree sprays of Release LC [predominantly gibberellic acid] (GA,) were applied in a commercial peach [Prunus perisca (L.) Batsch.] orchard in the California Central Valley on three dates from mid-June (about 90 days after full bloom = 28 days before harvest) to late July (14 days postharvest) 1993 at 50, 75, 100, and 120 mg·liter-1. Gibberellin (GA) reduced the number of flowers differentiated in 1993, thereby reducing fruit density in 1994, when spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 16 publications
4
35
0
3
Order By: Relevance
“…GA 3 treatments applied 7 WAA were reported to have moderate effects on fruit setting, while those applied 10 WAA were less effective; however, treatments conducted 13 WAA had the greatest effect, reducing fruit set by two-to threefold in comparison to that of control plants (Coneva and Cline, 2006). Hand-thinning requirements in the year after treatment were reported to be significantly reduced by the application of GA 3 sprays at 13 and 16 WAA, but thinning was not required at all for peach trees treated with GA 3 at anthesis (Southwick et al, 1995b). The present study demonstrated that as the concentration of GA 3 increased, the number of fruits in the following year's harvest decreased.…”
Section: Response To Ga 3 During the Subsequent Yearmentioning
confidence: 95%
See 1 more Smart Citation
“…GA 3 treatments applied 7 WAA were reported to have moderate effects on fruit setting, while those applied 10 WAA were less effective; however, treatments conducted 13 WAA had the greatest effect, reducing fruit set by two-to threefold in comparison to that of control plants (Coneva and Cline, 2006). Hand-thinning requirements in the year after treatment were reported to be significantly reduced by the application of GA 3 sprays at 13 and 16 WAA, but thinning was not required at all for peach trees treated with GA 3 at anthesis (Southwick et al, 1995b). The present study demonstrated that as the concentration of GA 3 increased, the number of fruits in the following year's harvest decreased.…”
Section: Response To Ga 3 During the Subsequent Yearmentioning
confidence: 95%
“…Gibberellins are thought to move from the fruit toward the nearest internode, thereby inhibiting the formation of fresh fruit buds 6-8 weeks after fruit setting (Webster and Spencer, 2000). Gibberellic acid treatment has been applied in apples (McArtney andLi, 1998), avocados (Salazar-García and, mangoes (Turnbull et al, 1996), citrus fruits (El-Otmani et al, 2000), apricots (Southwick et al, 1995a(Southwick et al, , 1997Southwick and Yeager, 1993), loquat (Reig et al, 2011), peaches and nectarines (Taylor and Geisler-Taylor, 1998;García-Pallas et al, 2001;Coneva and Cline, 2006;González-Rossia et al, 2007;Stern and Ben-Arie, 2009;Southwick et al, 1995b) and Japanese plums (González-Rossia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, since fruit thinning with chemical thinners in stone fruit is not as commercially efficient as in pome fruit (Byers et al, 2003), it became necessary to examine different concepts for fruit thinning at a much earlier stage of development, for example when flowering was initiated. Southwick et al (1995) found that GA 3 sprays on 'Loadel' cling peach trees at 90 DAFB reduced fruit yield in the following year. Gonzalez-Rossia et al (2007) also found similar trends in some Spanish peach and nectarine cultivars, although, like Southwick et al (1995), they had to use a high rate of GA 3 (≤ 100 mg l -1 GA 3 ) for good results.…”
Section: Discussionmentioning
confidence: 95%
“…However, hand-thinning is costly, and generally requires between 100 -500 h ha -1 , depending on tree vigour, age, size, flower production, thinning intensity, cultivar, and season (Southwick et al, 1995;1996). Alternative thinning techniques, such as mechanical approaches, chemical thinners (Byers et al, 1990;2003;Moran and Southwick, 2000;Fallahi et al, 2006), and inhibitors of photosynthesis (Byers et al, 1984), have been examined as substitutes for handthinning, but the thinning results were variable in stone fruit (Byers et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation